Un terrain miné, un travail de déminage ou comment parler de l’oppression des femmes minorisées en tant que chercheuse de la majorité - Iavarone-Turcotte, Anne (2023)
Dans cet article, je présente la manière dont j’ai abordé, pour tenter de les atténuer, les risques découlant de ma prise de parole sur mon objet d’étude doctorale : l’oppression des femmes dans les minorités religieuses. Ces risques découlant de mon positionnement de féministe blanche occidentale, membre de la majorité libérale et laïque, et détentrice de nombreux privilèges associés à ces statuts, j’ai résolu de modifier symboliquement ce positionnement dans ma recherche. Pour ce faire, j’ai élaboré et appliqué une méthodologie réflexive dont l’un des aspects clés, présenté dans l’article, a été de (re)tourner mon regard critique vers moi.
Keywords: 2000 à aujourd'hui; 2020-2029; amérique du nord; amériques; approches et analyses; cours; discipline; inégalités; justice sociale; phi4336; philosophie; point de vue situé; premier cycle; privilèges; pédagogie; périodes historiques; québec; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques

Réenchanter le monde: féminisme et politique des communs - Federici, Silvia; Linebaugh, Peter; Grunenwald, Noémie (Rupture, 2022)
« Silvia Federici présente une critique de la politique des communs dans une perspective féministe. De son vécu au Nigeria et de ses rencontres avec des militantes d'Amérique latine et du monde entier, Federici révèle les luttes quotidiennes des femmes contre la spoliation de leur terre, de leur logement et nourriture. De ses recherches historiques, elle compare les enclosures, qui ont permis la naissance du capitalisme par la destruction des communs et la prolétarisation des populations rurales, aux « nouvelles enclosures » au cœur de la phase actuelle d'accumulation capitaliste mondiale. Cet ouvrage soutient que les luttes autour de la reproduction sociale sont cruciales autant pour notre survie économique que pour la construction d'un monde libéré des hiérarchies et des divisions que le capital a implantées dans le corps du prolétariat international. Federici considère que les communs ne doivent pas être compris comme des îlots de partage dans un océans de relations d'exploitation, mais plutôt comme des espaces autonomes à partir desquels défier l'organisation capitaliste de la vie et du travail. »-- Quatrième de couverture.
Keywords: approches et analyses; com5170; communs; cours; discipline; droits des femmes*; féminisme matérialiste; histoire et politique; justice sociale; philosophie; philosophie politique; premier cycle; sciences humaines; thématiques

#MeToo and testimonial injustice: An investigation of moral and conceptual knowledge - Hänel, Hilkje C (Philosophy & Social Criticism, 2022)
Two decades ago, Tarana Burke started using the phrase ‘me too’ to release victims of sexual abuse and rape from their shame and to empower girls from minority communities. In 2017, actress Alyssa Milano made the hashtag #MeToo go viral. This article’s concern is with the role of testimonial practices in the context of sexual violence. While many feminists have claimed that the word of those who claim to being sexually violated by others (should) have political and/or epistemic priority, others have failed to recognize the harm and injury of instances of sexual violence that are not yet acknowledged as such and failed to listen to victims from marginalized social groups. In fact, some feminists have attacked #MeToo for mingling accounts of ‘proper’ sexual violence and accounts that are not ‘proper’ experiences of sexual violence. My aim in this article is to show why this critique is problematic and find a philosophically fruitful way to understand the #MeToo-movement as a movement that strives for moral and conceptual progress.
Keywords: #metoo; approches et analyses; cours; cycles supérieurs; discipline; fem9000; justice sociale; patriarcat; philosophie; racisme; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; violences sexistes et sexuelles; violences sexuelles

Le contrat sexuel - Pateman, Carole (La Découverte Poche, 2022)
« Par quel étrange paradoxe le contrat social, censé instituer la liberté et l'égalité civiles, a-t-il maintenu les femmes dans un état de subordination ? Pourquoi, dans le nouvel ordre social, celles-ci n'ont-elles pas accédé, en même temps que les hommes, à la condition d'« individus » émancipés ? Les théories du contrat social, héritées de Locke et de Rousseau, et renouvelées depuis Rawls, ne peuvent ignorer les enjeux de justice que soulève le genre. Carole Pateman montre, dans cet ouvrage désormais classique, que le passage de l'ordre ancien du statut à une société moderne du contrat ne marque en rien la ﬁn du patriarcat. La philosophe met ainsi au jour l'envers refoulé du contrat social : le « contrat sexuel », qui, via le partage entre sphère privée et sphère publique, fonde la liberté des hommes sur la domination des femmes. Il s'agit là moins d'exploitation que de subordination, comme le démontre l'autrice en analysant le contrat de mariage, mais aussi l'ensemble des contrats touchant à la propriété de la personne, de la prostitution à la maternité de substitution, jusqu'à l'esclavage et au salariat. Ainsi s'engage, à partir du féminisme, une critique de la philosophie politique libérale dans son principe même : pour Carole Pateman, un ordre social libre ne peut en aucun cas être de type contractuel. »-- Quatrième de couverture.
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; citoyenneté; contrat social; cours; discipline; droits des femmes*; fem1000; histoire et politique; incontournable; justice sociale; outils; ouvrages de références; patriarcat; phi4336; philosophie; philosophie politique; pol4212; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; science politique; science politique et droit; sciences humaines; systèmes d'oppressions; thématiques; théories féministes; violences; états-unis

Justice and the politics of difference - Young, Iris Marion; Allen, Danielle S. (Princeton classic editions, 2022)
"In this classic work of feminist political thought, Iris Marion Young challenges the prevailing reduction of social justice to distributive justice. The starting point for her critique is the experience and concerns of the new social movements that were created by marginal and excluded groups, including women, African Americans, and American Indians, as well as gays and lesbians. Young argues that by assuming a homogeneous public, democratic theorists fail to consider institutional arrangements for including people not culturally identified with white European male norms. Consequently, theorists do not adequately address the problems of an inclusive participatory framework. Basing her vision of the good society on the culturally plural networks of contemporary urban life, Young makes the case that normative theory and public policy should undermine group-based oppression by affirming rather than suppressing social group differences"
Keywords: 2000 à aujourd'hui; 2010-2019; amérique du nord; amériques; approches et analyses; cours; cycles supérieurs; discipline; discours dominant; fem9000; inégalités; justice sociale; phi4336; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; états-unis

La Conversation des sexes: philosophie du consentement - Garcia, Manon (Climats, 2021)
« L'affaire Weinstein et le mouvement #MeToo ont mis la question des violences sexuelles au premier plan. Depuis, le consentement renvoie naturellement au consentement sexuel et amoureux, envisagé comme un sésame de l'égalité entre femmes et hommes. Pourtant, il est bien difficile à définir, et soulève trois problèmes. Le problème juridique, bien connu de celles et ceux qui suivent l'actualité, peut être résumé ainsi : que faire pour que les cas de viol, d'agression et de harcèlement sexuels soient efficacement punis? Le deuxième problème est moral : comment penser des relations amoureuses et sexuelles qui ne soient pas fondées sur des normes sociales sexistes et inégalitaires? Enfin, le problème politique : comment ne pas reconduire les injustices de genre qui se manifestent dans les rapports amoureux et sexuels? La magistrale analyse du consentement que propose Manon Garcia revisite notre héritage philosophique, plongeant au cœur de la tradition libérale, mettant à nu ses impensés et ses limites. De John Locke aux théoriciennes féministes françaises et américaines, en passant par Michel Foucault et les débats sur la pratique du BDSM, c'est une nouvelle cartographie politique de nos vies privées que dessine cet essai novateur. Au terme de ce livre, il s'agira en somme, pour reprendre la formule de Gloria Steinem, d'« érotiser l'égalité » plutôt que la domination : en ce sens, le consentement sexuel, conçu comme conversation érotique, est sans doute l'avenir de l'amour et du sexe. »
Keywords: 2000 à aujourd'hui; approches et analyses; consentement; cours; discipline; droits des femmes*; europe; france; féminisme pop; justice sociale; metoo; phi4336; philosophie; premier cycle; périodes historiques; relations amoureuses; régions géographiques; sciences humaines; sexualité; thématiques

Applied epistemology - Lackey, Jennifer (Engaging philosophy, 2021)
Leading philosophers bring the tools of contemporary epistemology to bear on some of the most pressing social and political questions facing us as agents in the world today. This volume explores a diverse range of topics as they relate to epistemology under broad themes including injustice, race, feminism, sexual consent, and the internet.
Keywords: approches et analyses; corps; cours; cycles supérieurs; discipline; fem9000; histoire et politique; injustice; justice sociale; philosophie; sciences humaines; thématiques; violences; épistémologie; éthique

Connaître et s'engager par nos corps : analyse améliorative des corps par la phénoménologie, la cognition incarnée et le féminisme - Zimmermann, Camille (Université du Québec à Montréal, 2021)
Ce mémoire soutient une conception incarnée et dynamique de la connaissance, et ce, dans un cadre féministe afin d’analyser l’impact des structures sociales sur l’épistémologie. Nous chercherons à savoir si les corps peuvent être initiateurs de nouveaux paradigmes épistémiques pour les agent.e.s, grâce à des expériences uniques auxquelles ces corps nous donnent accès. Dû à un fort rationalisme en philosophie, le corps est souvent écarté de l’épistémologie ou réduit à un objet passif de connaissance. La dichotomie conceptuelle entre le corps et l’esprit, par exemple, sous-entend une représentation mécaniste et inerte des corps qui entraîne les agent.e.s à exclure leurs corps du processus de formation des connaissances, puisque la « matière » de manière considérée comme étant inerte. Notre hypothèse est que cette exclusion des corps renforce les injustices épistémiques que subissent certain.e.s agent.e.s. Nous tenterons de mettre en exergue au sein de la phénoménologie, des approches favorables à la cognition incarnée et propices à une compréhension améliorative des corps comme nous le retrouvons en études féministes. En nous inspirant de la méthode de Sally Haslanger et de certaines études sur la pratique de la danse, nous analyserons le concept de « corps » selon son utilité à la fois politique et épistémique, dans le but de clarifier et subvertir des mécanismes tacites d’oppression. À cet effet, nous proposerons un schéma en « V » du corps afin d’illustrer que les corps sont à la fois un engagement sensible et relationnel envers soi et le monde. Un engagement à partir duquel une perception, une compréhension et une action unique s’expérimentent. Ainsi, dans ce travail, nous proposons une épistémologie incarnée et dynamique, mais aussi une agentivité, elle-même incarnée à la fois au niveau épistémique que politique. _____________________________________________________________________________ MOTS-CLÉS DE L’AUTEUR : Corps, Épistémologie, Agentivité, Phénoménologie, Approches énactives, Études féministes, Injustice épistémique, Danse
Keywords: IREF; approches et analyses; corps; discipline; justice sociale; mémoires/thèses; philosophie; ressource en ligne; sciences humaines; thématiques; épistémologie

Metaepistemic Injustice and Intellectual Disability: a Pluralist Account of Epistemic Agency - Catala, Amandine (Ethical Theory and Moral Practice, 2020)
The literature on epistemic injustice currently displays a logocentric or propositional bias that excludes people with intellectual disabilities from the scope of epistemic agency and the demands of epistemic justice. This paper develops an account of epistemic agency and injustice that is inclusive of both people with and people without intellectual disabilities. I begin by specifying the hitherto undertheorized notion of epistemic agency. I develop a broader, pluralist account of epistemic agency, which relies on a conception of knowledge that accounts not only for propositional knowing, but also for other types of knowing that have been largely neglected in debates on epistemic injustice and agency. Based on this pluralist account of epistemic agency, I then show that people with intellectual disabilities qualify as epistemic agents and therefore as subjects of epistemic justice. Finally, I argue that this pluralist account of epistemic agency pushes us to revisit the current conception of epistemic injustice and to expand its taxonomy in two important ways.
Keywords: EDI; agentivité épistémique; approches et analyses; capacitisme; cours; cycles supérieurs; discipline; fem9000; handicap intellectuel; injustices épistémiques; inégalités; justice sociale; justice épistémique; philosophie; savoir propositionnel; sciences humaines; systèmes d'oppressions; taxonomie des savoirs; thématiques; violences; éthique

Par-delà les frontières du corps : repenser, refaire et revendiquer le corps dans le capitalisme tardif - Federici, Silvia ([Collection Cybernétique], 2020)
Comment reprendre corps? Comment nous rapporter au corps, cet objet éminemment historique, domestiqué, violenté, pathologisé? Silvia Federici répond: écoutons le langage du corps, sa fragilité et ses imperfections, afin de retrouver, par-delà ses frontières, la continuité magique qui nous relie aux autres êtres vivants qui peuplent la Terre. Mais surtout, identifions la plaie: les rapports sociaux de genre, de classe et de race. Dans cet ouvrage accessible et personnel, en dialogue avec les mouvements féministes contemporains, Silvia Federici entreprend d’extirper nos corps des pouvoirs et des dispositifs technologiques qui les aliènent et les transforment. Politiques de l’identité, chirurgie de transformation des corps, nouvelles technologies reproductives, ce livre examine avec lucidité ces questions brûlantes qui traversent le champ féministe.
Keywords: approches et analyses; corps; cours; discipline; fem3100; intersectionnalité; justice sociale; philosophie; premier cycle; rapports sociaux de sexe; sciences humaines; thématiques

L’inclusion du Black feminism dans la philosophie politique: une approche féministe de la décolonisation des savoirs - Berthelot-Raffard, Agnès (Recherches féministes, 2018)
Fondé sur ce que l’autrice nomme l’« approche féministe de la décolonisation des savoirs », cet article aborde la place du féminisme noir dans la philosophie politique. L’autrice montre que la pensée féministe noire est une philosophie de la justice sociale. À partir de la notion de « modestie épistémique » proposée par Eva Feder Kittay, l’autrice examine comment l’ignorance du système de valeurs et des expériences des femmes noires dans les théories libérales constitue une injustice herméneutique pour les intellectuelles qui édifient le Black feminism comme théorie de la justice raciale et de genre.
Keywords: afro-féminisme; amériques; approches et analyses; belgique; black feminism; canada; care; cours; discipline; europe; europe francophone; france; féminisme décolonial; féminismes noirs; histoire et politique; injustices herméneutiques; justice sociale; philosophie; philosophie politique; pol4212; premier cycle; québec; régions géographiques; sciences humaines; suisse; thématiques; éthique

The Routledge companion to feminist philosophy - Garry, Ann; Khader, Serene J.; Stone, Alison (Routledge philosophy companions, 2017)
"The Routledge Companion to Feminist Philosophy is an outstanding guide and reference source to the key topics, subjects, thinkers, and debates in feminist philosophy. Fifty-six chapters, written by an international team of contributors specifically for the Companion, are organized into five sections: (1) Engaging the Past; (2) Mind, Body, and World; (3) Knowledge, Language, and Science; (4) Intersections; (5) Ethics, Politics, and Aesthetics. The volume provides a mutually enriching representation of the several philosophical traditions that contribute to feminist philosophy. It also foregrounds issues of global concern and scope; shows how feminist theory meshes with rich theoretical approaches that start from transgender identities, race and ethnicity, sexuality, disabilities, and other axes of identity and oppression; and highlights the interdisciplinarity of feminist philosophy and the ways that it both critiques and contributes to the whole range of subfields within philosophy."--The publisher.
Keywords: afro-féminisme; approches et analyses; autonomie; bioéthique; care; cours; cycles supérieurs; discipline; environnement; esthétique; fem9000; féminisme africain; féminisme autochtone; féminisme décolonial; féminismes noirs; identité; injustices épistémiques; intersectionnalité; justice sociale; matérialité; objectivité; outils; ouvrages de références; philosophie; philosophie féministe; phénoménologie; politique de genre; queer; rationnalité; religion; sciences humaines; subjectivité; thématiques; théorie du contrat social; transféminisme; écologie; éthique; éthique du care; études critiques de la race; études critiques du handicap

Typecasts, Tokens, and Spokespersons: A Case for Credibility Excess as Testimonial Injustice - Davis, Emmalon (Hypatia, 2016)
Miranda Fricker maintains that testimonial injustice is a matter of credibility deficit, not excess. In this article, I argue that this restricted characterízation of testimonial injustice is too narrow. I introduce a type of identity-prejudicial credibility excess that harms its targets qua knowers and transmitters of knowledge. I show how positive stereotyping and prejudicially inflated credibility assessments contribute to the continued epistemic oppression of marginalized knowers. In particular, I examine harms such as typecasting, compulsory representation, and epistemic exploitation and consider what hearers are obligated to do in response to these injustices. I argue that because epistemic harms to rnarginatized knowers also arise from prejudicially inflated assessments of their credibility, the virtue of testimonial justice must be revised to remedy them.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; droits des personnes; excès de crédibilité; fem9000; fricker; injustices testimoniales; inégalités; justice sociale; philosophie; privilèges; sciences humaines; systèmes d'oppressions; thématiques; violences; éthique

Luttes féministes autour du consentement: Héritages et impensés des mobilisations contemporaines sur la gynécologie - Quéré, Lucile (Nouvelles Questions Féministes, 2016)
L'étude des mobilisations françaises de l'année 2014-2015 autour de la gynécologie permet d'interroger les différentes manières dont les mouvements féministes se sont saisis de la notion de consentement. Théorisé par les féministes à propos de la sexualité, le consentement est apparu comme un des principes fondateurs d'une morale sexuelle féministe. Les mouvements de 2014, portés par des militantes de la cause des femmes, (ré)introduisent cette notion dans le cabinet médical, et l'appliquent notamment à l'interaction gynécologique. Cela leur permet d'utiliser la loi française de 2002 sur les droits des patient·e·s comme un outil de politisation du cabinet gynécologique et de remise en cause des pratiques et des discours des soignant·e·s à l'égard des femmes.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; care; cours; discipline; discours dominant; europe; france; inégalités; justice sociale; militance; phi4336; philosophie; premier cycle; périodes historiques; régions géographiques; santé; santé des femmes*; sciences humaines; sexisme; sexualité; systèmes d'oppressions; thématiques

Traite, prostitution, inégalité - MacKinnon, Catharine A. (Collection Mobilisations, 2014)
De nos jours, il n'y a pas plus de prise de position favorable à la traite des êtres humains à des fins d'exploitation sexuelle qu'il y a de prise de position publique pour l'esclavage. Il est également très difficile de trouver des partisanes déclarées de l'inégalité… Ce n'est pourtant pas le cas de la prostitution. Certaines personnes sont pour la prostitution. Plus nombreuses sont celles qui considèrent politiquement correct de la tolérer. La plupart présument que, même si elle n'est pas réellement souhaitable, la prostitution est nécessaire, inévitable et sans dommage. Est-ce que la décriminalisation du proxénétisme et la légalisation des maisons closes assureront une plus grande sécurité physique aux personnes prostituées ? Contrairement à la Cour suprême du Canada, la juriste de réputation mondiale, Catharine A. Mac- Kinnon, répond négativement à cette question. Elle soutient que « loin de rendre la vie des prostituées plus sûre, la décriminalisation totale de la prostitution peut même la rendre encore plus dangereuse ». Pour cela, elle s'appuie sur les expériences des pays qui ont légalisé la prostitution et le proxénétisme et sur celles des pays, de plus en plus nombreux, qui décriminalisent les personnes prostituées et pénalisent les clients-prostitueurs ; la stigmatisation liée à l'activité Prostitutionnelle se retourne désormais contre ceux qui en profitent : les prostitueurs et les proxénètes.
Keywords: 2000 à aujourd'hui; amérique du nord; amériques; approches et analyses; canada; care; corps; cours; discipline; droits des femmes*; inégalités; justice sociale; patriarcat; phi2030; philosophie; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques; travail; travail du sexe; travail du sexe-prostitution; violences

Feminist, queer, crip - Kafer, Alison (Indiana University Press, 2013)
Select all Front Matter (pp. i-vi) Front Matter (pp. i-vi) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.1 Table of Contents (pp. vii-viii) Table of Contents (pp. vii-viii) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.2 Acknowledgments (pp. ix-xii) Acknowledgments (pp. ix-xii) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.3 Textual Description of the Cover Art (pp. xiii-xvi) Textual Description of the Cover Art (pp. xiii-xvi) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.4 Introduction: Imagined Futures (pp. 1-24) Introduction: Imagined Futures (pp. 1-24) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.5 I have never consulted a seer or psychic; I have never asked a fortune-teller for her crystal ball. No one has searched my tea leaves for answers or my stars for omens, and my palms remain unread. But people have been telling my future for years. Of fortune cookies and tarot cards they have no need: my wheelchair, burn scars, and gnarled hands apparently tell them all they need to know. My future is written on my body. In 1995, six months after the fire, my doctor suggested that my thoughts of graduate school were premature, if not misguided. He... 1 Time for Disability Studies and a Future for Crips (pp. 25-46) 1 Time for Disability Studies and a Future for Crips (pp. 25-46) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.6 What would it mean to explore disability in time or to articulate “crip time”? Temporal categories are already commonly used in formulations of disability; one aspect of cripping time might simply be to map the extent to which we conceptualize disability in temporal terms. The medical field in particular has a long tradition of describing disability in reference to time. “Chronic” fatigue, “intermittent” symptoms, and “constant” pain are each ways of defining illness and disability in and through time; they describe disability in terms of duration. “Frequency,” “incidence,” “occurrence,” “relapse,” “remission”: these, too, are the time frames of symptoms, illness,... 2 At the Same Time, Out of Time: Ashley X (pp. 47-68) 2 At the Same Time, Out of Time: Ashley X (pp. 47-68) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.7 In thinking about crip futurity, I find myself haunted by Ashley X. Born in 1997, the girl known as Ashley X was diagnosed with “static encephalopathy” a few months after her birth. “In the ensuing years,” doctors note, “her development never progressed beyond that of an infant,” and her doctors held no hope that her cognitive or neurological baseline would improve.¹ “At the age of 6 years, she [could] not sit up, ambulate, or use language.”² Concerned about their daughter’s long-term future, Ashley’s parents met with doctors in 2004 to discuss the potential effects of puberty and physical growth on... 3 Debating Feminist Futures: Slippery Slopes, Cultural Anxiety, and the Case of the Deaf Lesbians (pp. 69-85) 3 Debating Feminist Futures: Slippery Slopes, Cultural Anxiety, and the Case of the Deaf Lesbians (pp. 69-85) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.8 The pervasiveness of prenatal testing, and especially its acceptance as part of the standard of care for pregnant women, casts women as responsible for their future children’s able-bodiedness/able-mindedness; prospective parents are urged to take advantage of these services so as to avoid burdening their future children with any disabilities.¹ This notion of “burdening” children finds an echo in the debate over same-sex marriage, with LGBT couples cast as selfish parents, placing their own desires over the physical and mental health of their children (and, by extension, of all children). Moreover, according to Timothy Dailey of the Family Research Council, homosexual... 4 A Future for Whom? Passing on Billboard Liberation (pp. 86-102) 4 A Future for Whom? Passing on Billboard Liberation (pp. 86-102) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.9 “Super man,” the billboard exclaims, the unfamiliar gap between the two words emphasizing both the noun and its adjective. Below this phrase is the word “STRENGTH,” followed by the imperative “Pass It On.” At the bottom, in small print, runs the name and web address of the organization behind this public relations campaign: Values.com/Foundation for a Better Life. The “super man” referenced in the caption is, of course, the late Christopher Reeve, the white actor who starred in a series ofSupermanfilms in the 1980s before becoming a quadriplegic in a riding accident in 1995. A black-and-white photograph of... 5 The Cyborg and the Crip: Critical Encounters (pp. 103-128) 5 The Cyborg and the Crip: Critical Encounters (pp. 103-128) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.10 Controversy came quickly to the cyborg. In 1983,Socialist Reviewinvited several feminist theorists, among them Donna Haraway, “to write about the future of socialist feminism in the context of the early Reagan era.”¹ Haraway responded with “A Manifesto for Cyborgs,” framing the cyborg as a figure of feminist critique.² Her cyborg was a radical border-crosser, blurring the boundaries between human and animal, machine and organism, physical and non-physical.³ Such a cyborg, she argued, could “guide us to a more livable place,” an “elsewhere,” in which “people are not afraid of their joint kinship with animals and machines, not afraid... 6 Bodies of Nature: The Environmental Politics of Disability (pp. 129-148) 6 Bodies of Nature: The Environmental Politics of Disability (pp. 129-148) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.11 Although concern with the environment has long been an animating force in disability studies and activism, “environment” in this context typically refers to the built environment of buildings, sidewalks, and transportation technologies. Indeed, the social model of disability is premised on concern for the built environment, stressing that people are disabled not by their bodies but by their inaccessible environments. (The wheelchair user confronting a flight of steps is probably the most common illustration of this argument.) Yet the very pervasiveness of the social model has prevented disability studies from engaging with the wider environment of wilderness, parks, and nonhuman... 7 Accessible Futures, Future Coalitions (pp. 149-170) 7 Accessible Futures, Future Coalitions (pp. 149-170) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.12 When describing disability studies to my students, I often draw on Douglas Baynton’s insight that “disability is everywhere in history once you begin looking for it.”¹ For Baynton, “looking for it” entails not only recovering the stories of disabled people or tracing histories of disability discrimination but also exploring how notions of disability and able-mindedness/able-bodiedness have functioned in different contexts. Baynton issues his provocation to historians, but disability studies scholars in other fields have extended its reach, pushing their own colleagues to recognize disability as a category of analysis. Deeply influenced by and indebted to this work, I use this... Appendices (pp. 171-178) Appendices (pp. 171-178) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.13 Notes (pp. 179-224) Notes (pp. 179-224) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.14 Bibliography (pp. 225-252) Bibliography (pp. 225-252) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.15 Index (pp. 253-258) Index (pp. 253-258) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.16 Back Matter (pp. 259-259) Back Matter (pp. 259-259) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.17 Indiana University Press logo Front Matter Download XML Table of Contents Download XML Acknowledgments Download XML Textual Description of the Cover Art Download XML Introduction:: Imagined Futures Download XML Time for Disability Studies and a Future for Crips Download XML At the Same Time, Out of Time:: Ashley X Download XML Debating Feminist Futures:: Slippery Slopes, Cultural Anxiety, and the Case of the Deaf Lesbians Download XML A Future for Whom?: Passing on Billboard Liberation Download XML The Cyborg and the Crip:: Critical Encounters Download XML Bodies of Nature:: The Environmental Politics of Disability Download XML Accessible Futures, Future Coalitions Download XML Appendices Download XML Notes Download XML Bibliography Download XML Index Download XML Back Matter Download XML ABOUT US About JSTOR Mission and History JSTOR Labs JSTOR Daily News Webinars Careers EXPLORE CONTENT What's in JSTOR Advanced Search By Subject By Title Collections Publisher Images RESEARCH TOOLS Data for Research The JSTOR Understanding Series Constellate HELP CENTER Get Support Get Access LibGuides Research Basics Contact Us For Librarians For Publishers Teaching Resources JSTOR is part of ITHAKA, a not-for-profit organization helping the academic community use digital technologies to preserve the scholarly record and to advance research and teaching in sustainable ways.©2000‍–2024 ITHAKA. All Rights Reserved. JSTOR®, the JSTOR logo, JPASS®, Artstor®, Reveal Digital™ and ITHAKA® are registered trademarks of ITHAKA. Terms & Conditions of Use Privacy Policy Accessibility Cookie Policy Cookie Settings Description In Feminist, Queer, Crip Alison Kafer imagines a different future for disability and disabled bodies. Challenging the ways in which ideas about the future and time have been deployed in the service of compulsory able-bodiedness and able-mindedness, Kafer rejects the idea of disability as a pre-determined limit. She juxtaposes theories, movements, and identities such as environmental justice, reproductive justice, cyborg theory, transgender politics, and disability that are typically discussed in isolation and envisions new possibilities for crip futures and feminist/queer/crip alliances. This bold book goes against the grain of normalization and promotes a political framework for a more just world.
Keywords: 2000 à aujourd'hui; LGBTQIA2+; approches et analyses; care; corps; cours; crip; discipline; future; identités LGBTQIA2+; intersectionnalité; justice sociale; philosophie; premier cycle; périodes historiques; queer; ressource en ligne; santé; sciences de la santé; sciences humaines; sex1920; thématiques; études critiques du handicap

Relational Knowing and Epistemic Injustice: Toward a Theory of Willful Hermeneutical Ignorance - Pohlhaus, Gaile (Hypatia, 2012)
I distinguish between two senses in which feminists have argued that the knower is social: 1. situated or socially positioned and 2. interdependent. I argue that these two aspects of the knower work in cooperation with each other in a way that can produce willful hermeneutical ignorance, a type of epistemic injustice absent from Miranda Fricker's Epistemic Injustice. Analyzing the limitations of Fricker's analysis of the trial of Tom Robinson in Harper Lee's To Kill a Mockingbird with attention to the way in which situatedness and interdependence work in tandem, I develop an understanding of willful hermeneutical ignorance, which occurs when dominantly situated knowers refuse to acknowledge epistemic tools developed from the experienced world of those situated marginally. Such refusals allow dominantly situated knowers to misunderstand, misinterpret, and/or ignore whole parts of the world.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; fem9000; histoire et politique; ignorance herméneutique; injustices herméneutiques; injustices épistémiques; justice sociale; patriarcat; philosophie; privilèges; racisme; sciences humaines; systèmes d'oppressions; thématiques; éthique

La régulation sociale des minorités sexuelles: l'inquiétude dela différence - Corriveau, Patrice; Daoust, Valérie; ProQuest (Firme) (Les Presses de l'Université du Québec, 2011)
Successivement condamnées par la religion, criminalisées par le droit pénal et finalement médicalisées, les minorités sexuelles ont subi une forte répression institutionnelle. Depuis, les luttes des mouvements gais et lesbiens ont conduit, dans certains pays, à la reconnaissance des droits des homosexuels au mariage et à la parentalité. Toutefois, l’homosexualité est encore trop souvent perçue comme une menace à la tradition et à l’ordre « naturel ». Réunissant les contributions de chercheurs en sociologie, en philosophie, en criminologie, en histoire, en anthropologie, en sexologie et en travail social, cet ouvrage porte sur les multiples modes de régulation institutionnelle et sociale des minorités sexuelles. Tout en exposant les différentes pratiques de répression employées par le passé, les auteurs traitent de sujets contemporains comme l’homophobie dans les écoles et l’homoparentalité. Soulevant des questions de justice sociale, ils rappellent que tous, gais et lesbiennes y compris, sont engagés dans le processus de régulation des minorités sexuelles.
Keywords: LGBTQIA2+; amériques; anthropologie; approches et analyses; belgique; canada; cours; criminologie; discipline; europe; histoire; homophobie; hétérosexisme; justice sociale; militance; philosophie; premier cycle; queer; québec; régions géographiques; santé; sciences humaines; sexologie; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques; travail social; études gaies et lesbiennes

Qu'est-ce que la justice sociale?: reconnaissance et redistribution - Fraser, Nancy (Poche. Science humaines et sociales, 2011)
La reconnaissance est aujourd'hui un concept central du débat politique. Mais dans quelle mesure peut-elle s'intégrer à une réflexion normative sur la justice sociale ? C'est à cette question que répond la philosophe américaine Nancy Fraser, qui établit une distinction entre ce qu'elle appelle une politique de reconnaissance et une politique de redistribution. La première insiste sur l'égal respect dû à tous les membres d'une société, la seconde sur une redistribution équitable des biens et des ressources. Pour l'auteure, les conflits entre ces deux orientations sont politiquement paralysants et théoriquement insatisfaisants. En affirmant qu'une démocratie radicale consiste à reconnaître le caractère multiculturel et sexué des sociétés modernes, sans figer les identités des différents groupes ni renoncer à l'engagement historique de la gauche en faveur de l'égalité économique et sociale, elle vise à la réconciliation de la gauche culturelle et de la gauche sociale. Pour cette raison, cet ouvrage de philosophie politique est, à bien des égards, un livre politique.
Keywords: approches et analyses; cours; discipline; histoire et politique; justice sociale; militance; phi4336; philosophie; philosophie politique; sciences humaines; thématiques; théorie de la reconnaissance

The Relevance of Credibility Excess in a Proportional View of Epistemic Injustice: Differential Epistemic Authority and the Social Imaginary - Medina, José (Social Epistemology, 2011)
This paper defends a contextualist approach to epistemic injustice according to which instances of such injustice should be looked at as temporally extended phenomena (having developmental and historical trajectories) and socially extended phenomena (being rooted in patterns of social relations). Within this contextualist framework, credibility excesses appear as a form of undeserved epistemic privilege that is crucially relevant for matters of testimonial justice. While drawing on Miranda Fricker's proportional view of epistemic justice, I take issue with its lack of attention to the role that credibility excesses play in testimonial injustices. I depart from Fricker's view of the relation between credibility excesses and credibility deficits, and I offer an alternative account of the contributions that undeserved epistemic privileges make to epistemic injustices. Then, through the detailed analysis of To kill a mockingbird, I elucidate the crucial role played by the social imaginary in creating and sustaining epistemic injustices, developing an analysis of the kind of social blindness produced by an oppressive social imaginary that establishes unjust patterns of credibility excesses and deficits.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; droit; fem9000; histoire et politique; injustices épistémiques; inégalités; justice sociale; philosophie; privilèges; privilèges de crédibilité; science politique et droit; sciences humaines; systèmes d'oppressions; thématiques; éthique

Care, justice et dépendance : introduction aux théories du care - Garrau, Marie; Goff, Alice Le (Presses Universitaires de France, 2010)
Ce livre retrace le parcours théorique de la notion de dépendance dans la philosophie féministe contemporaine, de la critique du fonctionnement du concept dans la rhétorique de l’État libéral aux modalités de son inclusion dans une théorie de la justice. Deux axes se dégagent, qui convergent dans une tentative de redéfinition de la notion d’autonomie : les relations de dépendance constituent le point de départ de l’éthique du « care » ou de la sollicitude, qu’il s’agira de présenter ici ; elles ont en outre suscité des reformulations importantes des théories de la justice sur la base d’une anthropologie politique qui cherche à prendre acte de la constitution relationnelle des agents moraux. L’enjeu de ces réflexions n’est donc pas simplement de réévaluer la notion de dépendance, mais aussi de fournir un fondement normatif à l’inclusion des personnes dépendantes dans la communauté morale et politique, voire d’élaborer une conception renouvelée de la citoyenneté.
Keywords: approches et analyses; autonomie; capitalisme; care; discipline; justice sociale; philosophie; politiques néolibérales; projet charge mentale; ressource en ligne; sciences humaines; systèmes d'oppressions; thématiques; théorie du care

Contested pleasures: The sociopolitical economy of disability and sexuality - Shildrick, Margrit (Sexuality Research & Social Policy, 2007)
Consideration of sexual pleasure in the lives of people with disabilities plays little part in lay consciousness, and practically none in social policy. This article investigates such repression by engaging with a cultural imaginary that fears nonnormative sexuality as being a potential point of societal breakdown. Recent work in disability studies gives a very different understanding of the sexuate body that opens up the parameters of sexuality for everyone. This work challenges current social policy’s supposedly rational utilitarian basis and the principle of equality that together ground a sociopolitical economy of disability predicated on rehabilitation or compensation. Nonetheless, the call for sexual citizenship for people with disabi lities is fraught with difficulties, not least regarding the potential extension of govern mentality. An effective approach not only will take into account the sociopolitical aspects of this issue but also will respond to both the full embodiment of disability and its significance in mainstream culture.
Keywords: EDI; accessibilité; approches et analyses; arts; bioéthique; capacitisme; corps; cours; discipline; intersectionnalité; justice sociale; philosophie; premier cycle; ressource en ligne; sciences; sciences humaines; sex1911; sex1920; sexualité; systèmes d'oppressions; thématiques; études critiques du handicap; études littéraires

Anti-Essentialism and Intersectionality - Grillo, Tina (Theorizing feminisms a reader, 2006)
'What is oppression ?' 'What should be done about it ?' Organized around these questions, Theorizing feminisms : a reader provides an overview of theoritical feminist writing about the quest for gender justice. Incorporating both classic and cutting-edge material, the reader takes into account the full diversity of women, highlighting the effects of race, ethnicity, nationality, class, sexuality, and religion on women's experience. Theorizing feminisms is organized into four sections and includes fifty-four essays. The first section introduces several basic concepts commonly employed when thinking about sexism - oppression, social construction, essentialism, intersectionality, gender, race, and class - and also raises questions about the perspective and legitimacy of the theorist. The second section surveys three approaches that attempt to characterize in a general way the source of injustice toward women : humanist feminism ('the sameness approach'), gynocentric feminism ('the difference approach'), and dominance feminism. Offering an alternate perspective, the third section introduces two 'localizing' approaches, grounded in postmodernism and identity politics, respectively. Skeptical of theories that attempt to analyze social phenomena across history and culture, authors in this section challenge, rather than answer, the text's organizing questions. The final section explores the relationship of feminism theory to three liberatory projects - postcolonialism, neo-materialism, and queer theory - that do not characterize themselves as feminist, yet take gender as a significant category of analysis. Each section opens with an introduction and each essay is followed by helpful study questions. the majority of the essays are presented in their entirety. Theorizing feminisms underscores the strong connection between feminist theory and practice by including essays that illustrate important political inspirations or applications of each theoritical approach. It also presents versions of the same approach from various points in history, revealing feminist theory to be dynamic and evolving, rather than static. Ideal for interdisciplinary courses in feminist theory, this volume will also serve as an invaluable reference for current and future generations of theorists."
Keywords: 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; cours; discipline; essentialisme; intersectionnalité; justice sociale; phi4336; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; thématiques; théorie féministe

Privilege: Expanding on Marilyn Frye's "Oppression" - Bailey, A. (JOURNAL OF SOCIAL PHILOSOPHY -AUGUSTA-, 1998)
This essay serves as both a response and embellishment of Marilyn Frye's now classic essay " Oppression." It is meant to pick up where this essay left off and to make connections between oppression, as Frye defines it, and the privileges that result from institutional structures. This essay tries to clarify one meaning of privilege that is lost in philosophical discussions of injustice. I develop a distinction between unearned privileges and earned advantages. Clarifying the meaning of privilege as unearned structural advantage makes visible the role white privilege plays in maintaining complex systems of domination such as racism, sexism, heterosexism and classism. Using a critical reading of both Frye and Young's accounts of oppression as a springboard, I develop a definition of privilege as a particular class of unearned advantages. -/- I distinguish my account of privilege from standard legal and philosophical definitions of privilege. The general distinction I make between privileges and advantages rests on three interrelated claims: that benefits granted by privilege are always unearned and conferred systemically to members of dominant social groups; that privileges granted to members of dominant groups solely on the basis of their membership in these groups is never justifiable; and, that privileges have an unconditional value that can be explained not only in terms of immunities, but also in terms of additional benefits
Keywords: 1900-1999; 1990-1999; amérique du nord; amériques; approches et analyses; cours; cycles supérieurs; discipline; discours dominant; fem9000; justice sociale; phi4336; philosophie; premier cycle; privilèges; périodes historiques; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; états-unis